Halloysite Nanotubes (Hnts) Supported Candida Rugosa Lipase As Catalyst For Monoolein Production - Muhammad Shahrin, Nur Artikah (2020)
A growing demand for biofuels as the alternative to fossil fuel has produced abundance amount of crude glycerol as by-product. Utilization of crude glycerol into a value-added product such as monoolein has been the focus for this present work, as to provide alternative pathway to utilize the mass abandoned of crude glycerol from biodiesel industry.